Cleaning procedures in households, feasibility of biofilm formation (Research, Society and Development, 2026)
According to data from SINAN (Information System for Notifiable Diseases), between 2007 and 2016, 38.9% of outbreak cases in Brazil occurred in households, 16.2% in restaurants, and 7.9% in daycare centers and schools. Therefore, most outbreaks during this period took place in residences, probably due to a lack of knowledge about the basic requirements for proper food handling. Studies reveal that each year at least two billion people worldwide contract foodborne diseases, and that 87% of these outbreaks originate in the household environment. Given this context, the objective of this study was to assess the feasibility of biofilm formation in food handling areas within households. This study is experimental, cross-sectional research in which microbiological analysis of household surfaces was performed, and the conditions of conservation and quality of basic household utensils were observed. The results showed the frequent use of wooden utensils and utensils in poor states of conservation. Regarding microbiological parameters, the counts of aerobic mesophilic bacteria indicated inadequate cleaning conditions in most of the analyzed equipment, thereby enabling biofilm formation. It is concluded that there is a lack of information about food hygiene in households; the risks associated with wooden utensils or poorly maintained equipment are largely unknown, as is the proper application of adequate cleaning procedures.